N, N-Dimethyl Amine Linked to Triphenylamine (TPA): A Promising Co-Donor Moiety in Organic Dyes and their Push-Pull Behavior. - Ortiz G, Alejandro; Arcos, Wilmmer Alexander; Insuasty Obando, Braulio (Revista de Ciencias, 2013)
The push-pull behavior of novel codonor-donor dyes bearing a N,N-dimethyl amine linked covalently  to  a  triphenylamine  group  through  a  vinyl  bridge  was  studied  by  experimental (electrochemical and spectroscopic) analysis. These dyes were obtained by conventional reactions using a convergent synthesis method. An intra-molecular charge transfer process was observed in the electronic structure of these compounds.